Brunner & Suddarth's textbook of medical-surgical nursing - Hinkle, Janice L.; Cheever, Kerry H. (Philadelphia, Pennsylvania : Wolters Kluwer, 2018)
his textbook has been a favorite resource for students, instructors, and practicing nurses for almost a half-century. It's comprehensive yet accessible approach covers a broad scope of medical conditions while focusing strongly on the nurse's role in caring for, educating, and assisting patients and families.
Health care delivery and evidence-based nursing practice -- Community-based nursing practice -- Critical thinking, ethical decision making and the nursing process -- Health education and promotion -- Adult health and nutritional assessment -- Individual and family homeostasis, stress, and adaptation -- Overview of transcultural nursing -- Overview of genetics and genomics in nursing -- Chronic illness and disability -- Principles and practices of rehabilitation -- Health care of the older adult -- Pain management -- Fluid and electrolytes: balance and disturbance -- Shock and multiple organ dysfunction syndrome -- Management of patients with oncologic disorders -- End-of-life care -- Preoperative nursing management -- Intraoperative nursing management -- Postoperative nursing management -- Assessment of respiratory function -- Respiratory care modalities -- Management of patients with upper respiratory tract disorders -- Management of patients with chest and lower respiratory tract disorders -- Management of patients with chronic pulmonary disease -- Assessment of cardiovascular function -- Management of patients with dysrhythmias and conduction problems -- Management of patients with coronary vascular disorders -- Management of patients with structural, infectious, and inflammatory cardiac disorders -- Management of patients with complications from heart disease -- Assessment and management of patients with vascular disorders and problems of peripheral circulation -- Assessment and management of patients with hypertension -- Assessment of hematologic function and treatment modalities -- Management of patients with nonmalignant hematologic disorders -- Management of patients with hematologic neoplasms -- Assessment of immune function -- Management of patients with immune deficiency disorders -- Assessment and management of patients with allergic disorders -- Assessment and management of patients with rheumatic disorders. Assessment of musculoskeletal function -- Musculoskeletal care modalities -- Management of patients with musculoskeletal disorders -- Management of patients with musculoskeletal trauma -- Assessment of digestive and gastrointestinal function -- Digestive and gastrointestinal treatment modalities -- Management of patients with oral and esophageal disorders -- Management of patients with gastric and duodenal disorders -- Management of patients with intestinal and rectal disorders -- Assessment and management of patients with obesity -- Assessment and management of patients with hepatic disorders -- Assessment and management of patients with biliary disorders -- Assessment and management of patients with diabetes -- Assessment and management of patients with endocrine disorders -- Assessment of kidney and urinary function -- Management of patients with kidney disorders -- Management of patients with urinary disorders -- Assessment and management of female physiologic processes -- Management of patients with female reproductive disorders -- Assessment and management of patients with breast disorders -- Assessment and management of problems related to male reproductive disorders -- Assessment of integumentary function -- Management of patients with dermatologic problems -- Management of patients with burn injury -- Assessment and management of patients with eye and vision disorders -- Assessment and management of patients with hearing and balance disorders -- Assessment of neurologic function -- Management of patients with neurologic dysfunction -- Management of patients with cerebrovascular disorders -- Management of patients with neurologic trauma -- Management of patients with neurologic infections, autoimmune disorders, and neuropathies -- Management of patients with oncologic or degenerative neurologic disorders -- Management of patients with infectious diseases -- Emergency nursing -- Terrorism, Mass casualty, and disaster nursing.
Includes bibliographical references and index.
Keywords: NURSING CARE